Brief communication: Thwaites Glacier cavity evolution - Suzanne Bevan (The Cryosphere, 2021)
Between 2014 and 2017, ocean melt eroded a large cavity beneath and along the western margin of the fast-flowing core of Thwaites Glacier. Here we show that from2017 to the end of 2020 the cavity persisted but did not ex-pand. This behaviour, of melt concentrated at the groundingline within confined sub-shelf cavities, fits with prior observations and modelling studies. We also show that acceleration and thinning of Thwaites Glacier grounded ice continued, with an increase in speed of 400 m a−1and a thinning rate of at least 1.5 m a−1, between 2012 and 2020.